2014
DOI: 10.1007/s00167-014-2872-1
|View full text |Cite
|
Sign up to set email alerts
|

Modest mid-term outcomes after isolated arthroscopic debridement of acetabular labral tears

Abstract: Isolated arthroscopic labral debridement for hip labral tears had 45 % combined poor results when strictly defining failure as repeat surgery or abnormal hip rating. Untreated FAI and concomitant chondroplasty were risk factors for inferior outcome. We recommend concomitant treatment for bony impingement lesions and preservation of the labrum whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Although this finding was not carried over to other PROs, it is noteworthy and parallels some recent literature. Krych et al 29 reported 45% abnormal or severely abnormal hip function at a mean of 5 years after labral debridement. Schilders et al 30 retrospectively compared 69 labral repairs with 32 labral debridements and found significantly higher postoperative mHHS scores in the repair group.…”
Section: Discussionmentioning
confidence: 98%
“…Although this finding was not carried over to other PROs, it is noteworthy and parallels some recent literature. Krych et al 29 reported 45% abnormal or severely abnormal hip function at a mean of 5 years after labral debridement. Schilders et al 30 retrospectively compared 69 labral repairs with 32 labral debridements and found significantly higher postoperative mHHS scores in the repair group.…”
Section: Discussionmentioning
confidence: 98%
“…Twenty-four studies with 2692 patients (3125 hips) ultimately met criteria for inclusion in the review. Four studies reported on DEB alone,4 12 13 40 18 studies reported on OC,22 25 41–56 and two studies attempted a comparison between the two procedures 19 57…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Krych et al 13 retrospectively reviewed 57 patients who underwent isolated labral DEB with 2 years of follow-up to identify the reoperation rate and risk factors for poor outcome. Overall, 45% of patients either required a repeat surgery or subjectively rated their hips as abnormal or severely abnormal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Consequently, correction of labral tear by surgical labral reconstruction conferred superior results in comparison to labral debridement, in adequately restoring functional ability and reduce pain. [8][9][10][11][12] The labral reconstruction procedure uses a graft, either autograft or cadaveric allograft, and is a relatively recent procedure that has had encouraging outcomes.…”
Section: See Related Article On Page 1244mentioning
confidence: 99%